Disease X: combating the next pandemic needs the nifty wastewater-based epidemiology tool (2023)
he recent article [1] by Kate Bingham and Tim Hanes is a reminder and a warning that the next pandemic is inevitable, and it can potentially prove to be even more lethal than the last one. As noted by Kate Bingham and Tim Hanes, the flu pandemic in 1918–1919 caused an estimated 50 million deaths globally, and today one of the many viruses circulating have the potential to cause as much destruction internationally, this pathogen being Disease X.